2020
DOI: 10.5267/j.esm.2020.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Response of reciprocally supported advanced FRP composite jointed frames - Part 1: Experimental study

Abstract: This paper reports on a new experimental study for the behaviour of reciprocally connected and supported Fibre Reinforced Polymer (FRP) hollow square profiles axially loaded under several boundary conditions. The study aims to determine the ultimate load of the assembly and failure mechanism of mutually connected units. For the tests, FRP reciprocal frames units (RF) of 100 × 100 × 6.4 mm thick square hollow sections were designed, fabricated and assembled using mechanical fasteners. A bespoke steel test rig a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Badifu et al [ 38 ] investigated the failure mechanism of a pultruded FRP framework where joints were specifically analysed. Experimental results showed that the frame had an initial linear elastic behavior under vertical load, so the joints behaved elastically.…”
Section: Introductionmentioning
confidence: 99%
“…Badifu et al [ 38 ] investigated the failure mechanism of a pultruded FRP framework where joints were specifically analysed. Experimental results showed that the frame had an initial linear elastic behavior under vertical load, so the joints behaved elastically.…”
Section: Introductionmentioning
confidence: 99%